Ankle‐Brachial Index and Subsequent Risk of Severe Ischemic Leg Outcomes: The ARIC Study - Amy Paskiewicz (Wiley, 2021)
Background Ankle‐brachial index (ABI) is used to identify lower‐extremity peripheral artery disease (PAD). However, its association with severe ischemic leg outcomes (eg, amputation) has not been investigated in the general population. Methods and Results Among 13 735 ARIC (Atherosclerosis Risk in Communities) study participants without clinical manifestations of PAD (mean age, 54 [SD, 5.8] years; 44.4% men; and 73.6% White) at baseline (1987–1989), we quantified the prospective association between ABI and subsequent severe ischemic leg outcomes, critical limb ischemia (PAD with rest pain or tissue loss) and ischemic leg amputation (PAD requiring amputation) according to discharge diagnosis. Over a median follow‐up of ≈28 years, there were 221 and 129 events of critical limb ischemia and ischemic leg amputation, respectively. After adjusting for demographics, ABI ≤0.90 versus 1.11 to 1.20 had a ≈4‐fold higher risk of critical limb ischemia and ischemic leg amputation (hazard ratios, 3.85 [95% CI, 2.09–7.11] and 4.39 [95% CI, 2.08–9.27]). The magnitude of the association was modestly attenuated after multivariable adjustment (hazard ratios, 2.44 [95% CI, 1.29–4.61] and 2.72 [95% CI, 1.25–5.91], respectively). ABI 0.91 to 1.00 and 1.01 to 1.10 were also associated with these severe leg outcomes, with hazard ratios ranging from 1.7 to 2.0 after accounting for potential clinical and demographic confounders. The associations were largely consistent across various subgroups. Conclusions In a middle‐aged community‐based cohort, lower ABI was independently and robustly associated with increased risk of severe ischemic leg outcomes. Our results further support ABI ≤0.90 as a threshold diagnosing PAD and also suggest the importance of recognizing the prognostic value of ABI 0.91 to 1.10 for limb prognosis.